The DUF1996 and WSC domain‐containing protein Wsc1I acts as a novel sensor of multiple stress cues in Beauveria bassiana. (20th August 2019) - Tong, Sen‐Miao; Wang, Ding‐Yi; Gao, Ben‐Jie; Ying, Sheng‐Hua; Feng, Ming‐Guang
Abstract: Wsc1I homologues featuring both an N‐terminal DUF1996 (domain of unknown function 1996) and a C‐terminal WSC (cell wall stress‐responsive component) domain exist in filamentous fungi but have never been functionally characterized. Here, Wsc1I is shown to localize in the vacuoles and cell wall/membrane of the insect mycopathogen Beauveria bassiana and hence linked to cell membrane‐ and vacuole‐related cellular events. In B. bassiana, deletion of Wsc1I resulted in marked increases of hyphal and conidial sensitivities to hyperosmotic agents, oxidants, cell wall perturbing chemicals, and metal cations (Cu 2+, Zn 2+, Fe 2+, and Mg 2+ ) despite slight impact on normal growth and conidiation. Conidia produced by the deletion mutant showed not only reduced tolerance to both 45°C heat and UVB irradiation but also attenuated virulence to a susceptible insect through normal cuticle infection or cuticle‐bypassing infection. Importantly, phosphorylation of the mitogen‐activated protein kinase Hog1 was largely attenuated or nearly abolished in the Wsc1I ‐free cells triggered with hyperosmotic, oxidative, or cell wall perturbing stress. All changes were well restored by targeted gene complementation. Our findings highlight a novel role of Wsc1I in sensing multiple stress cues upstream of the Hog1 signalling pathway and its pleiotropic effects in B. bassiana .